The Effect Of Capital Structure, Profitability and Liquidity on Firm Value With Dividend Policy As A Moderating Variable - Arafah Esa Yuswandani; Naelati Tubastuvi; Akhmad Darmawan; Ika Yustina Rahmawati (Universitas Muhammadiyah Sorong, 2023)
Goals of this study are to see if there is an effect of capital structure, profitability and liquidity on firm value by including dividend policy as a moderation variable. In this study, a quantitative approach was chosen. This study’s population includes all companies in the LQ45index from periode 2018-2021 and purposive sampling is used in this research sampling techniques. Multiple regression analysis and the absolute difference test were used in this study. According to the findings of this study, capital structure has no effects on firm alue, profitability has positive effects on firm value, and liquidity has positive effects on firm value, dividend policy as moderation is not able to moderate the effect of capital structure on firm value, dividend policy variable as moderation is unable to moderate the effect of profitability on firm value also liquidity on firm value cannot moderate by dividend policy.